Ligand-bridged charge extraction and enhanced quantum efficiency enable efficient n–i–p perovskite/silicon tandem solar cells. Issue 8 (8th July 2021) - Aydin, Erkan; Liu, Jiang; Ugur, Esma; Azmi, Randi; Harrison, George T.; Hou, Yi; Chen, Bin; Zhumagali, Shynggys; De Bastiani, Michele; Wang, Mingcong; Raja, Waseem; Allen, Thomas G.; et al.
Abstract : 27%-efficient perovskite/silicon tandem solar cells are achieved in n–i–p configuration by developing novel electron and hole selective contacts, which combine high broadband transparency with efficient charge extraction. Abstract : Translating the high power conversion efficiencies of single-junction perovskite solar cells in their classic, non-inverted (n–i–p) architecture to efficient monolithic n–i–p perovskite/silicon tandem solar cells with high current densities has been a persistent challenge due to the lack of low-temperature processable, chemically-insoluble contact materials with appropriate polarity and sufficient optical transparency. To address this, we developed sputtered amorphous niobium oxide (a-NbO x ) with ligand-bridged C60 as an efficient electron-selective contact, deposited on the textured-silicon bottom cell. For the sunward, hole-selective contact we implemented a stack of molecularly doped broadband transparent evaporated 2, 2′, 7, 7′-tetra( N, N -di- p -tolyl)amino-9, 9-spirobifluorene (spiro-TTB) and atomic layer deposited vanadium oxide, which further enhances the device quantum efficiency. Combining these contact materials with two-dimensional perovskite passivation on the micrometer-thick solution-processed perovskite top cell yields 27% efficient monolithic n–i–p perovskite/silicon tandem solar cells, which represents one of the highest power conversion efficiencies reported on pyramidal textured crystalline silicon bottom cells, and the highest with this polarity.